Global Health Education in UK Medical Schools (GHEMS) study protocol. (2019) - Bandyopadhyay, Soham; Shortland, Thomas; Wadanamby, Shavinthi W; Thomas, Hannah S; Gurung, Binay; Akhbari, Melika; Trout, Isobel; Patel, Rashida; Sharma, Karisma; Fitzgerald, J Edward; Smith, Adrian D
No abstract available